أسباب مساءلة رئيس الدولة في دساتير الجزائر ،المانيا والولايات المتحدة الأمريكية - بلجاني, وردة (جامعة الوادي University of Eloued, 2019)
إنطلاقا من مبدأ أن كل سلطة تقابلها مسؤولية تقع على عاتق من يمارسها ، فإن المشرع الدستوري الجزائري أقرّ بمسؤولية رئيس الجمهورية مقابل سلطاته في نصوص دستوره لسنة 1996 ، المعدل في سنة 2016 على غرار ما أخذت به دساتير النظم البرلمانية الجمهورية كدستور ألمانيا لسنة 1949 والنظم الرئاسية كدستور الولايات المتحدة لسنة 1789 من خلال هذا الدراسة نحاول ان نتعرف عن الأسباب التي حددها كل من مشرعي الدساتير السالفة الذكر والتي يترتب عنها إثارة المسؤولية الدستورية لرؤساء دولهم. Abstract: Starting from the principle that each authority has a responsibility which falls on those who exercise it, the Algerian constitutional legislator acknowledged the responsibility of the President of the Republic in return for his powers in the texts of 1996's constitution which was amended in 2016, similar to what was taken by constitutions of the Republican parliamentary systems as Germany's Constitution of 1949 and presidential systems such as the United States Constitution of 1789. Through this study, we try to identify the reasons identified by each of the legislators of above-mentioned constitutions and which consequence raise of constitutional responsibility for their heads of State .
Keywords: رئيس الدولة؛مسؤولية دستورية؛الخيانة العظمى؛إنتهاك قانون؛الإتهام الجنائي; The head of State; constitutional responsibility ; high treason; violating the law;Impeachment